Observation of deep oscillation usage and its effectiveness on burn scars – case report - Pogorzelska, Justyna A.; Zaglaniczny, Dominik; Zmyślna, Anna; Kiebzak, Wojciech (Medical Studies/Studia Medyczne, 2017)
An organism that has undergone tissue damage pursues its immediate recovery. In order to do so, it uses a dynamic and congeneric process of regeneration consisting of several phases. Currently, innovative methods are being sought influencing tissue healing. One such system is deep oscillation, which is based on an intermittent electrostatic field created between the device and the patient’s skin. It causes a unique, deep, and resonant vibration. It is a noninvasive and painless method. The aim of deep oscillation is purposeful interfering in the physiological processes of tissue trophism. In the thesis, the case of 16-month-old girl is presented, who experienced a thermal scald to her left arm and her chest. The aim of the following thesis is observation of deep oscillation use and its effectiveness in the event of newly formed burn scars that undergo remodelling and can lead to curtailment of the healing process.